The Role of Principals' Leadership in Improving the Professional Competence of Teachers in Sekolah Luar Biasa (SLB) - Rina Aulina; Maman Suherman; Agus Ruswandi (Dinasti Publisher, 2025)
This study explores the role of principals’ leadership in enhancing the professional competence of teachers in special education (Sekolah Luar Biasa/SLB) in Indonesia. Teacher competence in special education is a critical factor in ensuring the quality of learning for students with disabilities. At the same time, school principals hold a central position in creating supportive environments for teachers' professional growth. Despite the theoretical consensus regarding the importance of instructional and transformational leadership, a significant gap remains in understanding how these leadership practices are operationalized in resource-constrained special education contexts. To address this issue, the research employed a qualitative multiple-case study design at SLB A YPKR Cicalengka, Bandung Regency, and SLB BC Al Barkah, Garut Regency. Data were collected through in-depth interviews, participant observation, and document analysis, and subsequently analyzed using Miles and Huberman’s interactive model with source and methodological triangulation to ensure data validity. The findings reveal that effective leadership in SLB is not confined to a single model but rather a dynamic integration of participative, instructional, transformational, and distributed approaches. Principals demonstrated adaptability by combining planning, organizing, implementation, and evaluation functions with collaborative and reflective practices. Limited financial and infrastructural resources were addressed through creative strategies, internal capacity building, and partnerships with external stakeholders. Importantly, principals’ leadership fostered teacher motivation, ownership, and commitment, resulting in sustainable professional development. In conclusion, the study emphasizes that visionary and adaptive school leadership is essential for enhancing teacher competence in special education. The implications extend to leadership preparation programs and educational policy, underscoring the need for context-sensitive, holistic leadership models to improve the quality of education for children with special needs.